Open tubular capillary electrochromatography with an N‐phenylacrylamide‐styrene copolymer‐based stationary phase for the separation of anomers of glucose and structural isomers of maltotriose. Issue 10 (2nd April 2015) - Ali, Faiz; Cheong, Won Jo
Abstract : A ligand with a terminal halogen (4‐chloromethylphenyl isocyanate) was chemically bound on the inner surface of pretreated silica capillary with 50 μm internal diameter and 58 cm total and 50 cm effective length in the presence of dibutyl tin dichloride as a catalyst through isocyanate‐hydroxyl reaction. Attachment of initiator (sodium diethyl dithiocarbamate) to the bound ligand was carried out and followed by in situ polymerization. Reversible addition‐fragmentation chain transfer polymerization was used for the immobilization of N ‐phenylacrylamide‐styrene copolymer on the inner surface of capillary column. The resultant open tubular column showed excellent separation performance for derivatized saccharide isomers in capillary electrochromatography.d ‐Glucose was separated into α‐ and β‐anomers while five structural isomers were separated for derivatized maltotriose with separation efficiency above one million theoretical plates per meter. The effects of pH and acetonitrile composition on the electrochromatographic performance of the derivatized saccharides were studied and the optimized elution condition was found to be 90:10 v/v% acetonitrile/30 mM sodium acetate at pH 6.6. UV absorption at 214 nm was used as detection mode in open tubular capillary electrochromatography separations.